Numerical Solutions of Fractional Differential Equations - Avcı, İbrahim (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
In this thesis, we focus on numerical solutions of general linear multi-term fractional differential equations (FDEs) with fractional derivatives defined in the Caputo sense. Multi-term fractional order differential equations are involving both ordinary and fractional derivative operators. Numerical methods plays very crucial role for solving fractional differential equations, since analytical solutions are not always possible for solving them. Memory trait of fractional calculus is one of the main reason for difficulty of developing analytical techniques for such a equations. Therefore, there has been considerable interest in solving FDEs numerically in recent years and many powerful schemes have been developed. Essentially, most of the developed methods are modified from original versions for classical differential equations and applied to FDEs. In this study, we introduce a numerical technique based on the fractional Taylor vector and we construct fractional Taylor operational matrix of fractional integration to solve multi-term FDEs. The main characteristic of this technique is to reduce the given IVP of fractional order to a system of algebraic equations by employing the fractional Taylor operational matrix of fractional integration. Finally, this set of algebraic equations can be solved easily and efficiently for unknown coefficients by using computer programming. Consequently, by using these coefficients, the approximate solution of the given problem can be obtained. Some numerical examples are presented to demonstrate the accuracy and applicability of given method. The approximate solutions obtained by use of given technique are compared with numerical results of some other methods in literature and exact solutions of given problems. From these results, we can conclude that the presented technique is efficient and applicable for solving high order multi-term fractional order differential equations numerically. Keywords: numerical solutions, fractional Taylor vector,fractional differential equations, spectral method, Caputo fractional derivative, Riemann-Liouville fractional integral, operational matrices.

OZ: Bu tez c¸alıs¸masında, Caputo kesirli t¨urevlerine sahip, genel lineer c¸ok terimli kesirli diferansiyel denklemlerin sayısal y¨ontem ile c¸ ¨oz¨umlerine odaklanılmıs¸tır. C¸ ok terimli kesirli t¨urevlere sahip diferansiyel denklemler, hem klasik hem kesirli t¨urev operat¨orleri ic¸eren denklemlerdir. Analitik metodlar ile kesirli t¨urevlere sahip diferansiyel denklemlerin c¸ ¨oz¨umlerine ulas¸mak her zaman m¨umk¨un olmadı˘gından, sayısal metodlar bu t¨ur denklemlerin c¸ ¨oz¨umlerinde c¸ok ¨onemli bir rol oynamaktadır. Kesirli analizin uzun hafıza ¨ozelli˘gi, bu t¨ur diferansiyel denklemlerin c¸ ¨oz¨um¨u ic¸in analitik y¨ontemler gelis¸tirmeyi zorlas¸tıran en ¨onemli sebeplerden biridir. Bu nedenle, kesirli t¨urevli diferansiyel denklemlerin sayısal y¨ontemler kullanılarak c¸ ¨oz¨um¨u son yıllarda b¨uy¨uk ilgi g¨ormektedir ve bunun sonucu olarak birc¸ok g¨uc¸l¨u teknik gelis¸tirilmis¸tir. Aslında, gelis¸tirilen y¨ontemlerin c¸o˘gu, klasik diferansiyel denklemlerin c¸ ¨oz¨um¨u ic¸in kullanılan orijinal versiyonlardan de˘gis¸tirilip g¨uncellenerek kesirli diferansiyel denklemlere uygulanan y¨ontemlerdir. Bu c¸alıs¸mada, c¸ok terimli kersirli diferansiyel denklemlerin sayısal c¸ ¨oz¨umleri ic¸in, kesirli Taylor vekt¨or¨une dayanan bir y¨ontem sunulmaktadır. Sunulan y¨ontemin ana amacı, kesirli Taylor vekt¨or¨unden yararlanarak kesirli integrasyonun operasyonel matrisini olus¸turmak ve bu matrisi kullanarak, verilen c¸ok terimli kesirli diferansiyel denklemin bir cebirsel denklem sistemine indirgenmesini sa˘glamaktır. Son olarak, elde edilen bu cebirsel denklem sistemi, bilgisayar programlaması kullanılarak, bilinmeyen katsayı ic¸in verimli bir bic¸imde c¸ ¨oz¨ulebilmektedir. Sonuc¸ olarak, elde edilecek katsayılar kullanılarak, verilen problemin yaklas¸ık c¸ ¨oz¨um¨u elde edilmektedir. Sunulan y¨ontemin verimlili˘gini ve uygulanabilirli˘gini test edebilmek ic¸in bazı ¨ornekler verilmis¸tir. Sunulan y¨ontem kullanılarak elde edilen yaklas¸ık c¸ ¨oz¨umler, verilen problemlerin kesin c¸ ¨oz¨umleri ve literat¨urde bulunan bazı di˘ger sayısal y¨ontemler ile kars¸ılas¸tırılmıs¸tır. Elde edilen sonuc¸lar ve kars¸ılas¸tırmalar, sunulan y¨ontemin, c¸ok terimli kesirli diferansiyel denklemlerin yaklas¸ık c¸ ¨oz¨umlerine ulas¸makta c¸ok bas¸arılı ve verimli oldu˘gunu kanıtlamaktadır. Anahtar Kelimeler: sayısal c¸ ¨oz¨umler, kesirli diferansiyel denklem, spektral metod, Caputo kesirli t¨urevi, Riemann-Liouville kesirli integrali, kesirli Taylor vekt¨or¨u, operasyonel matrix.
Doctor of Philosophy in Applied Mathematics and Computer Science. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2020. Supervisor: Prof. Dr. Nazim Mahmudov.
Keywords: Mathematics; Applied Mathematics and Computer Science; Differential Equations; Numerical solutions; fractional Taylor vector; fractional differential equations; spectral method; Caputo fractional derivative; Riemann-Liouville fractional integral; operational matrices